Pengaruh Ancaman, Risiko, dan Strategi Pengamanan Terhadap Keamanan Data Pribadi pada Pengguna E-Commerce - Khotimah, Siti (Maliki Interdisciplinary Journal, 2025)
E-commerce is a form of online commerce where customers provide personal information such as name, address, phone number, credit card number, etc. If that information falls into the wrong hands, then the user can suffer financial loss or even have their identity stolen and misused by irresponsible people. Threats to personal information security in e-commerce include criminal or advanced attacks that threaten users’ security, privacy and crime. The impact of these threats to personal data security in e-commerce is substantial and impacts both business owners and customers. The risks associated with personal data security in e-commerce can lead to data breaches that can be detrimental to both users and e-commerce service providers. Implementing the right security strategies can help protect personal data and other critical information from cyber-attacks. Tokopedia’s use of OTP (One Time Password) is one example of a security strategy that can help protect personal data. The better the security strategy used, the lower the risk of cybercrime against personal data. Therefore, both e-commerce business owners and users must have a good security strategy to ensure the safety of personal data.